Managing change in collective action and collective identity to sustain Community Based Natural Resources Management (CBNRM) institutions in Namibia: A case study of Doro !Nawas Conservancy (Namibian Journal for Research, Science and Technology, 2020)
Conservation and community development are increasingly understood to require sustained collective action. This study postulates collective action and collective identity as necessary but vulnerable in the management of Community Based Natural Resources Management (CBNRM) institutions. The study uses purposive and snowball sampling to select key informants interviews and documentary analysis to augment the comprehensiveness. Conservancy members (47) and individuals from non-governmental organisations (NGOs) and government (9) with experience and knowledge of the conservancy were interviewed. The study adopted a thematic analysis approach with deductive analysis to interrogate the data. The adaptation framework based on the identification and affective commitment was used to organise and present the findings. The findings reveal the casual factors and excerpts that best described how respondents articulated change and stability in the identification and affective commitment. The paper concludes that for CBNRM institutions to function effectively management should be sensitive to heterogeneity within the collective. It further concluded that management should be aware of how members of the collective express themselves and be mindful of the nuances of the language they use. Lastly, management should appreciate that government and other agencies by acting as ‘honest brokers’ they can contribute to sustaining the collective action and collective identity in CBNRM and similar institutions.
Keywords: Job satisfaction; organisational citizenship behaviour; satisfaction with life